ANALISIS DAMPAK HIDROLOGI PERUBAHAN TUTUPAN LAHAN BERDASARKAN RENCANA TATA RUANG WILAYAH: STUDI KASUS DAS SAMBONG KABUPATEN BATANG - Nugraha, Mustofa Fajar; Hidayat, Reza Januar; Indriyani, Retno Ajeng Mega (Bapelitbang Kabupaten Batang, 2025)
Floods are the most common disasters in Central Java, caused by rapid urbanisation and land-use changes. This research utilises HEC-HMS continuous simulation to assess the impact of land-use planning on runoff behaviour in the Sambong Watershed, Batang Regency. The analysis compares land cover data from 2017 and 2023 with the spatial pattern projection of the 2019-2039 Spatial Plan, using daily rainfall data from 2014 to 2023. Model calibration and validation yielded satisfactory results (NSE 0.553 to 0.655, R2 0.65 to 0.67, PBIAS -5.81 to 3.47, RSR 0.668 to 0.587). Results show that increased built-up areas lead to higher peak discharges, increased runoff volume, and high flow (Q5%, Q10%, Q20%) increase, while low flow (Q80%, Q90%, Q95%) decrease, indicating increased flood risk during rainy seasons and higher drought susceptibility during dry periods. Sub-watersheds S5 and S7 experience the most significant increases in built-up areas, at 78.57% and 213.24%, respectively, with peak discharge increases of 4.20% and 27.37%. These findings suggest that the current spatial plan may exacerbate flood hazards and reduce dry season water availability, underscoring the need for improved land-use controls and integrated watershed management to ensure sustainable development and water resource conservation in Batang Regency.